2000
DOI: 10.3390/50300422
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant Activity Evaluation of Withanolides from Jaborosa integrifolia

Abstract: Antifeedant activity of the 4-deoxi-27-hydroxi-withanolides (1, 2 y 3) isolated from Jaborosa integrifolia (Solanaceae) was investigated in caterpillar Spodoptera littoralis on Leaf Disk Choice Bioassay. Results indicate that the best feed inhibition effect is due to Jaborosalactone A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In this case, only jaborosalactone P (389) produced a significant delay in the development of neonate larvae. In the case of J. integrifolia, only jaborosalactone A (487) exhibited antifeedant activity on larvae of Spodoptera littoralis (206). Rearrangement of the epoxide to the allylic alcohol as in jaborosalactone B (488) or cleavage to the diol as in jaborosalactone D (489) resulted in complete loss of the activity.…”
Section: Antifeedant and Growth Inhibitionmentioning
confidence: 99%
“…In this case, only jaborosalactone P (389) produced a significant delay in the development of neonate larvae. In the case of J. integrifolia, only jaborosalactone A (487) exhibited antifeedant activity on larvae of Spodoptera littoralis (206). Rearrangement of the epoxide to the allylic alcohol as in jaborosalactone B (488) or cleavage to the diol as in jaborosalactone D (489) resulted in complete loss of the activity.…”
Section: Antifeedant and Growth Inhibitionmentioning
confidence: 99%
“…These structures belong to a class of pyranoisoquinolines known as Cassiarines (A-J), which are also found in the extracts of the Cassia family 37 . Yet another compound predicted to be potentially binding to the main protease is 5,6-dihydro, 5α-chloro-6β-hydroxy-Jaborosalactone 5 [CNP0252890], one of several jaborosalactones 38 ; naturally-occurring Withanolide chlorohydrins found in the extracts of species in the genus Jaborosa that have been reported to act as insect anti-feedants 39 . These plants are members of the Solanaceae family and are widely distributed throughout South America, but primarily in the Andes region.…”
Section: Discussionmentioning
confidence: 99%
“…The whole plant of N. physaloides is used as medicine, especially as a sedative, expectorant, antipyretic, and antidote in China [ 138 , 139 ]. Phytochemical studies revealed that N. physaloides contained large amounts of withanolides [ 140 , 141 ] and aromatic glycosides [ 142 ], with anti-tumor [ 143 ], anti-inflammatory [ 144 ], and other pharmacological effects. Because of the medicinal property of this herb, Peng Zhang isolated two new withanolides, 165 – 166 ( Figure 23 ), and evaluated them for their inhibitory effects on NO production induced by LPS in a mouse macrophage cell line RAW 264.7, using hydrocortisone and dexamethasone as positive controls.…”
Section: Withanolides As Anti-inflammatory Agentsmentioning
confidence: 99%